IMPLEMENTASI PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA KARYAWAN PT. MULIA LESTARI - Irfan Saefuloh (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2021)
In carrying out activities in organizations and companies, competent human resources are needed in their fields. This article discusses the implementation of hr training and development in improving employee performance at PT. Mulia Lestari. The importance of training and developing human resources to improve employee performance. This research is qualitative descriptive, using data collection techniques by observation, interview and documentation studies and data processing is carried out through the process of analysis, display, and further verification of data. Based on the results of data processing, research was obtained that the implementation of training and development conducted by PT. Mulia Lestari using Power Character (PC), in this system is not only the implementation of training and development but ranging from recruiting planning to appraisal assessment. Appraisal is done not only by superiors but also by colleagues and subordinates with the composition of the assessment in accordance with the position of position. Appraisal system consists of assessment of character, competence, contribution and commitment. Appraisal in 2017 the most significant contribution indicator with a weighting of 40% compared to other assessment indicators. Dalam melaksanakan kegiatan dalam organisasi maupun perusahaan, dibutuhkan SDM yang kompeten di bidangnya. Artikel ini membahas mengenai implementasi pelatihan dan pengembangan SDM dalam meningkatkan kinerja karyawan di PT. Mulia Lestari. Pentingnya pelatihan dan pengembangan sumber daya manusia untuk meningkatkan kinerja karyawan. Penelitian ini bersifat deskriptif kualitatif yaitu menggunakan teknik pengumpulan data dengan cara observasi, wawancara dan studi dokumentasi serta pengolahan data dilakukan melalui proses analisis, display, dan selanjutnya verifikasi data. Berdasarkan hasil pengolahan data, diperoleh penelitian bahwa implementasi pelatihan dan pengembangan yang dilakukan PT. Mulia Lestari menggunakan Power Character (PC), dalam system ini bukan hanya pelaksanaan mengenai pelatihan dan pengembangan namun mulai dari perencanaan recruitmen hingga penilaian appraisal. Appraisal ini penilain dilakukan bukan hanya oleh atasan tetapi juga oleh rekan kerja dan bawahan dengan komposisi penilaian sesuai dengan posisi jabatan. Appraisal system terdiri dari penilaian karakter, kompetensi, kontribusi dan komitmen. Apraisal pada tahun 2017 indikator kontribusi paling signifikan dengan bobot 40 % dibanding indikator penilaian lainnya.